Bidirectional Paper-Repository Tracing in Software Engineering - Garijo, Daniel; Arroyo, Miguel; Gonzalez, Esteban; Treude, Christoph; Tarocco, Nicola (Proceedings (IEEE/ACM International Conference on Mining Software Repositories. Online), 2024)
While computer science papers frequently include their associated code repositories, establishing a clear link between papers and their corresponding implementations may be challenging due to the number of code repositories used in research publications. In this paper we describe a lightweight method for effectively identifying bidirectional links between papers and repositories from both LaTeX and PDF sources. We have used our approach to analyze more than 14000 PDF and Latex files in the Software Engineering category of Arxiv, generating a dataset of more than 1400 paper-code implementations and assessing current citation practices on it.CCS CONCEPTS*Applied computing → Document analysis; * Software and its engineering → Software libraries and repositories.